HERBAL SHAMPOO INNOVATION: PURWACENG EXTRACT AS THE MAIN ACTIVE INGREDIENT - Windari, Nur Azizah; Nafisah, Rahma; Nisa, Izatin; Kurniawan, Anang (Sentra Kekayaan Intelektual dan Inovasi Teknologi (INOTEK) Universitas Sains Al-Qur'an, 2024)
Shampoo is a hair care product commonly used by the general public with the main ingredient being surfactant/detergent (Pravitasari et al., 2021). Some people experience hair health issues such as dandruff and hair loss caused by hormonal changes in the body, dirty hair, and infrequent shampooing, or the use of inappropriate shampoo products. This article aims to present an innovation in shampoo using Purwaceng extract. Purwaceng (Pimpinella pruatjan) is an indigenous Indonesian herbal rich in properties, found in the highlands of Dieng, Central Java. Purwaceng contains active antioxidant compounds including flavonoids, alkaloids, saponins, and tannins (Andrian, 2021). These compounds make Purwaceng potentially effective in preventing dandruff, stimulating hair growth, maintaining scalp health, and addressing hair loss. The research method involves formulation to determine the optimal composition and formula, using three sample preparations (F0, F1, and F2) that undergo stability testing. The conclusion is that the shampoo with the appropriate formula exhibits good stability for hair and is safe, as demonstrated by Sample F1. The results of this study are expected to provide information on the stability and safety of Purwaceng extract as a shampoo raw material. Additionally, it is hoped that the public can utilize Purwaceng to develop innovative shampoo products with further potential for development .